A nationwide survey of pediatric acquired demyelinating syndromes in Japan. (8th November 2016) - Yamaguchi, Y.; Torisu, H.; Kira, R.; Ishizaki, Y.; Sakai, Y.; Sanefuji, M.; Ichiyama, T.; Oka, A.; Kishi, T.; Kimura, S.; Kubota, M.; Takanashi, J.; et al.
Abstract : Objective: To investigate the clinical and epidemiologic features of pediatric acquired demyelinating syndromes (ADS) of the CNS in Japan. Methods: We conducted a nationwide survey and collected clinical data on children with ADS aged 15 years or younger, who visited hospitals between 2005 and 2007. Results: Among 977 hospitals enrolled, 723 (74.0%) responded to our inquiries and reported a total of 439 patients as follows: 244 with acute disseminated encephalomyelitis (ADEM), 117 with multiple sclerosis (MS), 14 with neuromyelitis optica (NMO), and 64 with other ADS. We collected and analyzed detailed data from 204 cases, including those with ADEM (66), MS (58), and NMO (10). We observed the following: (1) the estimated annual incidence rate of pediatric ADEM in Japan was 0.40 per 100, 000 children (95% confidence interval [CI], 0.34–0.46), with the lowest prevalence in the north; (2) the estimated prevalence rate of MS was 0.69 per 100, 000 children (95% CI, 0.58–0.80), with the lowest prevalence in the south; (3) NMO in Japan was rare, with an estimated prevalence of 0.06 per 100, 000 children (95% CI, 0.04–0.08); and (4) the sex ratio and mean age at onset varied by ADS type, and (5) male/female ratios correlated with ages at onset in each ADS group. Conclusions: Our results clarify the characteristic clinical features of pediatric ADS in the Japanese population.